Methods of the Dehydration Process and Its Effect on the Physicochemical Properties of Stingless Bee Honey: A Review - Liyana Nabihah Ikhsan; Kok-Yong Chin; Fairus Ahmad (Molecules, 2022)
Stingless bee honey (SLBH) has a high moisture content, making it more prone to fermentation and leading to honey spoilage. Dehydration of SLBH after harvest is needed to reduce the moisture content. This review compiles the available data on the dehydration methods for SLBH and their effect on its physicochemical properties. This review discovered the dehydration process of vacuum drying at 60 °C and 5% moisture setting, freeze-drying at −54 °C and 5% moisture setting for 24 h, and using a food dehydrator at 55 °C for 18 h could extract >80% water content in SLBH. As a result, these methods could decrease moisture content to <17% and water activity to <0.6. These will prevent the fermentation process and microorganism growth. The hydroxymethylfurfural (HMF) contents remain within the permissible standard of <40 mg/kg. The total phenolic content increased after dehydration by these methods. Therefore, dehydration of SLBH is recommended to increase its benefits.